Komunikasi Transendental : Dalam Buku Panduan Sholat Khusuk Karya DR. Sa'id Bin Ali Bin Wafh Al-Qahthani - Mardiyah, Mardiyah; Syarifudin, Achmad; Aji Isnaini, Modh (CV. ITTC INDONESIA, 2023)
This thesis is entitled